Initiating an Oral History Project in a Multicultural UNESCO World Heritage Site of George Town, Penang, Malaysia: Challenges and Outcomes - Mahani Musa,; Kuah Li Feng, (Kajian Malaysia, 2016)
The recognition accorded to George Town as UNESCO World Heritage Site on 7 July 2008 has opened a new challenge for the state government in terms of heritage management and town planning. As the listing was conducted on the basis of a "living" cultural site, the government has since initiated several moves to safeguard the city's intangible cultural heritage. One such initiative comes from the George Town World Heritage Incorporated (GTWHI) which initiated a pilot oral history documentation project in 2013. Using the project as a case study, this paper seeks to illustrate the role of an oral history project in creating public awareness and appreciation for heritage as well as in encouraging community engagement in the heritage discourse.